Indonesia's Legal Remedies for Violation of Diplomatic Immunity for Interception of the Indonesian Embassy in Yangon - Eryana, Fikar; Putri, R. Eriska Ginalita Dwi (Dinasti Research, 2025)
This study analyzes Indonesia's legal efforts against the violation of diplomatic immunity due to the wiretapping of the Embassy of the Republic of Indonesia (KBRI) in Yangon, Myanmar in June 2004. The incident violated Article 22 and Article 27 of the 1961 Vienna Convention, as eavesdropping devices were found in the Ambassador's office and diplomatic communication cables, which undermined the principles of inviolability and freedom of communication. This study uses a descriptive qualitative research method used with a juridical-normative approach based on literature studies from primary, secondary, and tertiary legal materials. The findings show that Myanmar has neglected to carry out its diplomatic protection obligations, so the recipient country is obliged to be held internationally responsible through compensation, apologies, or improvement of security procedures in accordance with the provisions of the International Law Commission Draft Articles on State Responsibility and the Principle of Responsiveness The Indonesian State chooses a settlement through peaceful diplomatic channels, including formal negotiations and protests, in accordance with the spirit of ASEAN and Article 33 of the UN Charter. However, its effectiveness depends on Myanmar's good faith to improve the protection system of diplomatic facilities and provide assurance that similar incidents do not recur. This study confirms the importance of strengthening international legal mechanisms in maintaining the integrity of bilateral relations and the reputation of global diplomacy.